(Invited) Enhancement of Surface Oxygen Exchange Kinetics for Pr0.1Ce0.9O2-δ with Deposition of La or Sm Oxide. (13th April 2015) - Zhao, Liang; Perry, Nicola H.; Sasaki, Kazunari; Bishop, Sean R.
Abstract : Rapid oxygen transport across the gas/solid interface (oxygen exchange) is critical for solid oxide fuel cell electrode performance. In this work, La and Sm are shown to dramatically improve the oxygen exchange rate on Pr0.1 Ce0.9 O2-δ thin films (>50 x at 450 o C) as compared to a freshly deposited film without La or Sm oxide. A surface cleaning effect from the La and Sm is suspected as the source of the enhancement, though catalytic activity from La and Sm may also play a role.